Differences in reading comprehension in 4th and 5th grade students of elementary school in two municipalities in the Valley region of the state of Jalisco, Mexico - González-B., Víctor (2015)
Reading comprehension (RC) is one of the most important behavioral competencies for modern man. Those who do not read or read without understanding are unable to use the knowledge that, figuratively speaking, are available in the texts. This situation is common to a lot of students in elementary school in Mexico, more acute in those who live in non-urban areas. In this sense we did a study to assess the level of RC in 4th and 5th grade students of elementary school in two municipalities in the state of Jalisco, because there is no specific data about it. 112 students of 4th and 5th grade participated, 56 participants for each group, who were evaluated for their RC with ECOMPLEC test (Leon Escudero and Olmos, 2012). The results showed no statistically significant differences in RC between students of 4th and 5th grade (t test with p > 0,05), although the latter group had better results. We also found that in both groups of students most of them had a RC that was from very low to médium level. The need for intervention programs to improve the quality of education of students in marginal areas is discussed.